Upaya Pemerintahan Kabupaten Bima Dalam Melibatkan Masyarakat Membangun Wisata Lariti Di Kecamatan Sape Kabupaten Bima (Studi Kasus Pada Dinas Pariwisata Kabupaten Bima) - Mustamin H. Idris; Nidya Putri Syahida; Andi Ardyansyah (Universitas Muhammadiyah Mataram, 2018)
Tourism is one of the most reliable sectors in national development, tourism also plays a role in creating employment and reducing unemployment. This is evidenced by the contribution of the tourism sector to the workforce in 2015 12.1 million people or 10.6% of the total national workforce, to support the tourism sector there is a need for community participation and professionalism from the government in providing tourism development policies in accordance with government regulations and provisions in the Republic of Indonesia Law Number 10 of 2009 concerning tourism. Departing from these conditions, the researchers tried to analyze the efforts of the Bima District Government in involving the community to build Lariti tourism in the Sape District of Bima Regency. The purpose of this study, to find out the efforts of the Bima District Government in involving the community to develop Lariti tourism, along with the factors that support and inhibit the Bima Regency Government in an effort to involve the community to develop Lariti tourism, the method used in this research is qualitative descriptive method with data collection techniques using interviews and documentation. The results showed that the efforts of the Bima Regency Government in involving the community in developing Lariti tourism in Sape Subdistrict were positive, this shows that qualitatively the Bima Regency Government through the Bima Tourism and Culture Office involved the community actively in Lariti tourism development, besides behavior community and infrastructure Larites are a supporting factor and a barrier for the Bima District Government to involve the community in developing Lariti tourism in the Sape District of Bima Regency.